Peptidomics approaches to the discovery and ACE inhibitory effect of casein peptides derived from fermented bovine milk by kefir grains - Wang, Bo; Xiao, Shan; Cai, Yanxue; Chen, Xuan; Wang, Jihui (Frontiers in Sustainable Food Systems, 2023)
Kefir grains with efficient proteolytic system is an excellent starter culture for the production of bioactive peptides and milk products.In the present study, the casein in bovine milk was fermented by kefir grains. Peptidomics based on the LC-MS/MS was used to investigate the dynamic profile and the structure specificity of generated peptides. The angiotensin converting enzyme (ACE) inhibitory activity of the fermented products was also determined. The results indicated that the cell envelope proteinases (CEPs) were the P I -/P III -type. A total of 122 peptides were identified. The β-casein was preferentially hydrolyzed by kefir grains, and the main hydrolysis regions were f57-93, f132-160 and f192-209. The αs1-, and κ-casein were also hydrolyzed by a weaker degree. In the process of fermentation, the accumulated peptides increased with the fermentation time. The fermentation products exhibited ACE inhibitory activity, and this bioactivity remained 63% after simulated gastrointestinal (GI) digestion in vitro. Additionally, 14 Pro-containing peptides with ACE inhibitory activity were also identified. These results provide new insights and evidence to investigate the bioactive milk peptides generated by kefir grains fermentation, as well as a reference for the development of functional foods.